2017
DOI: 10.1364/oe.25.023312
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength- and OAM-tunable vortex laser with a reflective volume Bragg grating

Abstract: Vortex beams carrying orbital angular momentum (OAM) have been recently investigated intensely in optical communication systems, as using OAM mode multiplexing simultaneously with other conventional multiplexing techniques is the key to further expand data capacity. This article demonstrates a wavelength- and OAM-tunable vortex laser at 1.6 µm in an Er:YAG system. For the first time to the best of our knowledge, a reflective volume Bragg grating (VBG) was theoretically and experimentally proved to be an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In 2017, Lyubopytov et al 162 designed a micro-electro-mechanical (MEMS) filter system realizing vortex generation with a wavelength-tunable width of 37.5 nm and an OAM of 0~3ℏ. In the same year, Liu et al 163 reported a ring-pumped Er:YAG solid-state laser generating an 8.4-nm wavelength-tunable width and 0~±2ℏ OAM-tunable VB. In 2018, Yao et al 164 invented a new optical fibre combiner for combining two polarization-controllable fundamental modes into a VB with chiral control, obtaining a 30-nm wavelength-tunable width and 0~±1ℏ OAM.…”
Section: Progress In Vortex Generation Tuning and Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Lyubopytov et al 162 designed a micro-electro-mechanical (MEMS) filter system realizing vortex generation with a wavelength-tunable width of 37.5 nm and an OAM of 0~3ℏ. In the same year, Liu et al 163 reported a ring-pumped Er:YAG solid-state laser generating an 8.4-nm wavelength-tunable width and 0~±2ℏ OAM-tunable VB. In 2018, Yao et al 164 invented a new optical fibre combiner for combining two polarization-controllable fundamental modes into a VB with chiral control, obtaining a 30-nm wavelength-tunable width and 0~±1ℏ OAM.…”
Section: Progress In Vortex Generation Tuning and Manipulationmentioning
confidence: 99%
“…Wang’s group 168 designed and implemented a fibre-space coupling vortex laser system, where a wavelength-tunable range of 1530–1565 nm and an OAM of 0~±10ℏ were achieved.
Fig. 9Generation of wavelength- and OAM-tunable CW VBs (I).Generation methods of wavelength- and OAM-tunable VBs using an acousto-optic fibre grating ( a ), along with the experimental results 161 ( b ), an SPP-embedded MEMS filter system 162 ( c – e ), and a VBG in a hollow-pumped solid-state laser 163 ( f ). Reprinted with permission from refs.
…”
Section: Progress In Vortex Generation Tuning and Manipulationmentioning
confidence: 99%
“…Conclusively, we can actively control the OAMs among the range from 1ℏ to 15ℏ with wavelength-tunable width about 10 nm. Compared with a recent work in which an Er:YAG solid-state vortex beam was OAM and wavelength tunable by a VBG [5] with the OAMs range of 0; 1ℏ; 2ℏ and the wavelength-tunable width of 4.9 nm, our dual-off-axis-pumped Yb:CALGO system without any other modulating element provides more remarkable results.…”
mentioning
confidence: 80%
“…Vortex beams carrying orbital angular momentum (OAM) have drawn ever-increasing interest in recent years, giving rise to a wide range of applications such as optical communications [1,2], particle manipulation [3], and quantum entanglement [4]. For the sake of scaling the application of high-capacity and multi-channel optical communications, researchers are currently pursuing the wavelength-and OAM-tunable vortex lasers with large spectral tunable range [5][6][7][8]. Some approaches have been reported that use volume Bragg grating (VBG) [5], metasurfaces [6], wavelength division multiplexing (WDM) [7], or intracavity polarization transformers [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation